2019
DOI: 10.3390/w11071421
|View full text |Cite
|
Sign up to set email alerts
|

Local Scour of Armor Layer Processes around the Circular Pier in Non-Uniform Gravel Bed

Abstract: Flume experiments have been carried out under clear water scour conditions to analyze the maximum equilibrium scour depth and scour processes in armored streambeds. A total of 85 experiments have been carried out using different diameters of circular piers and non-uniform gravels. A graphical approach for dimensionless scour depth in equilibrium condition around the circular pier in armored streambeds has been developed. As per this curve, the maximum dimensionless scour depth variation with dimensionless armo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Within the same river environment, sediment erosions can occur on the riverbed, on the side-bank of the river and even on some local areas, such as those around the piers that are built along the river to support the bridges. Pandey et al [45] conducted experiments to analyze the maximum equilibrium between the scour depth and the scour process in an armored streambed. It was found that the variation of the maximum dimensionless scour depth with the dimensionless armor particle size depends on the densimetric particle Froude number (Fr d50 ).…”
Section: Summary Of This Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Within the same river environment, sediment erosions can occur on the riverbed, on the side-bank of the river and even on some local areas, such as those around the piers that are built along the river to support the bridges. Pandey et al [45] conducted experiments to analyze the maximum equilibrium between the scour depth and the scour process in an armored streambed. It was found that the variation of the maximum dimensionless scour depth with the dimensionless armor particle size depends on the densimetric particle Froude number (Fr d50 ).…”
Section: Summary Of This Special Issuementioning
confidence: 99%
“…It was found that the variation of the maximum dimensionless scour depth with the dimensionless armor particle size depends on the densimetric particle Froude number (Fr d50 ). Sediments are eroded and transported by the water along the river and their deposition, suspension and transport are regulated and continuously modified by the turbulence and other flow structures [45]. To provide better understanding on the coupled effects of sediment inertia and stratification on the pattern of secondary current in bend-flows, a study was published by Yang et al [46] to evaluate a full 3D numerical model.…”
Section: Summary Of This Special Issuementioning
confidence: 99%
“…Several studies for pier and abutment scours were completed by researchers over non-uniform sediment beds [15][16][17][18][19][20][21][22]. However, very few studies are available for non-uniform gravel beds.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, it was observed that the turbulent characteristics at the upstream of the scour hole were negative, while the occurrence of downward seepage stabilizes the reversal of the flow and results in reduced turbulence characteristics. Pandey et al [21] conducted flume experiments under clear-water scour conditions and analyzed the equilibrium pier scour processes in non-uniform gravel beds. They proposed a graphical method for calculating the maximum scour depth under an equilibrium condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation